The role of fine needle aspiration cytology in breast mass management - حســـين تيســـير (Latakia University Journal -Medical Sciences Series, 2021)
Objective:Experiencing the efficacy of fine needle aspiration cytology, as a primary procedure in diagnosing breast mass in cytology setting. Material and methods:Reviewing cytology reports of 129 patients and comparing the results with following histopathology findings for the same patients or following benign FNAC cases for at least 6 months. From false positive and false negative cytology findings, sensitivity, specificity, positive and negative predicting value were calculated. Results:Out of 129 cytology results, 92 cases showed negative FNA of malignancy. Following up those cases revealed 4 malignant cases (false negative cytology). 25 malignant cytology reports revealed 2 benign histology findings (false positivity). Suspicious FNAC (12) had only one malignancy. From the above findings, FNAC sensitivity 82%, specificity 87%, positive predictive value 92%, and negative predictive value 95.5%. Conclusion:Fine needle aspiration cytology is an efficient procedure for diagnosing breast mass, especially, when its performed in combination with clinical and radiological assessments (triple diagnostic procedure).